1999
DOI: 10.1128/iai.67.9.4931-4934.1999
|View full text |Cite
|
Sign up to set email alerts
|

Virulence ofMycobacterium tuberculosisCDC1551 and H37Rv in Rabbits Evaluated by Lurie’s Pulmonary Tubercle Count Method

Abstract: The virulence of the CDC1551 strain of Mycobacterium tuberculosis was compared to that of H37Rv in a rabbit inhalation model. While rabbits that inhaled the two strains produced equal numbers of grossly visible primary tubercles, CDC1551 tubercles were smaller and contained fewer bacilli than H37Rv tubercles. These findings suggest that a miniepidemic near the Kentucky-Tennessee border caused by CDC1551 was due not to increased virulence but to increased transmissibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…These strains belong to the Euro‐American lineage (principal genetic group 2, cluster IV). For this reason, strain CDC1551, which has been extensively characterized in terms of its biology 47–51 and belongs to the same group but different cluster ( i.e . cluster V) was included in this study as a reference for S75 strains.…”
Section: Discussionmentioning
confidence: 99%
“…These strains belong to the Euro‐American lineage (principal genetic group 2, cluster IV). For this reason, strain CDC1551, which has been extensively characterized in terms of its biology 47–51 and belongs to the same group but different cluster ( i.e . cluster V) was included in this study as a reference for S75 strains.…”
Section: Discussionmentioning
confidence: 99%
“…However, rabbits are still an excellent animal model for human TB vaccine research because of the similar manifestations of lesions (granulomas, liquefaction, and cavities) to those observed in humans [14,15]. In particular, rabbit models have been extensively used to screen and evaluate potential vaccine candidates (such as BCG, M. vaccae, M. microti and subunit vaccines), and to determine the pathogenic factors and pathogenesis of cavities induced by M. tuberculosis H37Rv infection [15][16][17][18][19][20]83]. In addition, Tsenova et al [84] reported large confluent granulomas with expansive areas of central necrosis in the lungs of rabbits infected with M. tuberculosis HN878 strain.…”
Section: Rabbitsmentioning
confidence: 99%
“…Because CDC1551 induced vigorous TST reactions despite occasionally minor exposure, it was initially considered to be a virulent strain. Further analysis revealed CDC1551 to be of no greater virulence in animals than other strains in terms of its growth in vitro and in vivo (30). However, it was found to induce a marked proinflammatory cytokine response in mononuclear phagocytes: a mechanism proposed to underlie the marked TST responses that were observed (17).…”
Section: Discussionmentioning
confidence: 99%